VISUALIZATION EVALUATION WITH THE RAPID MINER APPLICATION USING THE C4.5 ALGORITHM - Rachmi Syafira Putri Lubis (INFOKUM, 2023)
Evaluation of data visualization using the RapidMiner application and the C4.5 algorithm is an important research area to gain a better understanding of patterns and trends in data. RapidMiner, as a well-known science and data analysis platform, provides a wide range of data analysis and visualization tools and techniques. The C4.5 algorithm is a method used to generate decision trees and is used in many machine learning applications for classification. This study aims to evaluate how these two technologies can be used together for data analysis and visualization. The research methodology involves data collection, pre-processing, application of the C4.5 algorithm, data visualization, and results evaluation. The results of this study indicate that using RapidMiner and the C4.5 algorithm simultaneously can produce informative and easy-to-understand data visualizations. This allows researchers and professionals to better understand patterns and trends in data, and aids in data-driven decision making. However, this study also found that there are challenges in understanding and implementing the C4.5 algorithm in the context of RapidMiner, which requires specific knowledge and expertise. Overall, this research makes an important contribution to the field of data science, providing guidance and recommendations for the use of RapidMiner and the C4.5 algorithm in the context of data analysis and visualization.